Effect of Superior Varieties and Insecticides on Pest Control and Food Safety of Groundnut (Arachis hypogaea L.) - Prihatin Prihatin; Nurul Wiridannisaa; Tamrin Abdullah (Universitas Islam Raden Rahmat, Malang, 2025)
Groundnut (Arachis hypogaea L.) is a vital protein source supporting nutrition and sustainable farming, yet its productivity in Indonesia remains low due to pests and poor cultivation.This study aims to evaluate the effectiveness of a combination of superior varieties and types of insecticides in suppressing pest populations and increasing yields. The research was conducted in Sambueja Village, Maros Regency, using a Randomized Group Design (RAK) with four treatments: A1 (local seed + deltamethrin chemical insecticide), A2 (local seed + bogenvil vegetable insecticide), B1 (Takar 2 + chemical insecticide), and B2 (Takar 2 + vegetable insecticide), each with three replications. Results indicated that treatment B1 gave the highest yields: plant height 45 cm, number of leaves >20, wet weight 287.42 g, and number of pods 286.93 per plant. Treatment B2 was also high: 261.98 g wet weight and 261.49 pods. Treatments with local varieties gave lower yields. The use of improved varieties such as Takar 2, especially in combination with effective insecticides, is proven to increase productivity. However, chemical insecticides risk leaving residues that impact natural enemies, health, and the environment. In contrast, plant-based insecticides, while slower, are an environmentally friendly alternative that supports sustainable and safe agriculture.